Time differential perturbed angular correlation (TDPAC) study of some hafnium glycolate complexes - Barbiéri, Roberto Santos [UNESP]; Klein, Stanlei I. [UNESP]; Netto, Antonio Marques (Elsevier B.V., 1988)
Time differential measurements of the 133-482 keV γ-γ angular correlation of 181Ta have been performed in solid hafnium complexes of the type [Hf(glycol)4] (glycol = p-chloromandelate, p-bromomandelate, b-naphthylglycolate and mandelate). The quadrupolar frequencies (ωQ) were found to increase within the series. This behaviour was explained by supposing a dissipation of electronic density at the metal level, caused by an increase in intermolecular hydrogen bonding in the complexes throughout the series studied. These results seem to agree with complementary data from IR spectroscopic studies. © 1988.